Persepsi Santri Pondok Pesantren Darussalam Terhadap Bank Syariah Indonesia - Hidayat Darussalam (Sharia Economic and Management Business Journal (SEMBJ), 2021)
The purpose of this research is to identify the santri perception toward syaria bank and to analyze the perception of santri between pesantren one with other pesantren. The questionnaire contains the profiles and perceptions of santri towards sharia banks. To analyze the santri's perception level in general and to compare the santri perception level between one pesantren with other pesantren using Factor Analysis with Lisrel 8.54. The conclusions of this study are 1) The level of students' perception of Islamic banks is proportionally relatively the same. The level of perception is almost owned by students (47.5%), good and very good perceptions (44.1%), and less (8.3%). For the future, sharia banks should conduct socialization to pesantren because pesantren is a big potential for the development efforts of sharia banks in Indonesia.